Impacts of Thermal Maturity on the Carbon Isotopes of Hopane Compounds in Lacustrine Shale During Compaction Pyrolysis Experiments - Lu Li; Yan Liu; Xing Wang; Yaohui Xu; Zhigang Wen; Haowei Chen; Gang Yan; Zhongdeng Lu; Zulin Chen; Zeyang Guo (Applied Sciences)
The carbon isotopic behavior of hopane compounds during thermal maturation remains ambiguous due to limitations in current detection techniques. In this study, a low-maturity lacustrine shale sample was pyrolyzed in a hydrous semi-open pyrolysis system. The hopane compounds from the artificially matured samples (Ro = 0.72–1.28%) have been separated and enriched for the test of their carbon isotopes (δ13C). The results show that thermal maturity can somewhat affect the carbon isotopes of monomeric hopane compounds, with a maximum difference value over 21‰. However, thermal maturity has different effects on the δ13C values for different monomeric hopane compounds. For example, the carbon isotopic values of 22S-homohopane at different thermal stages can vary up to 21‰, while only 3‰ for C29βα. In addition, the carbon isotopes of different monomeric hopane compounds show distinct evolution trends. For C29αβ and C29 Ts, their carbon isotopes first become slightly heavier and then become lighter, reaching the lightest value at 350 °C. When the pyrolysis temperature continues to increase, the δ13C values become heavier and finally become lighter. However, the δ13C values of Ts, Tm, 22S-homohopane, and 22R-homohopane show a completely reversed trend. They initially become slightly lighter and then become heavier, reaching the maximum value at 350 °C. When the pyrolysis temperature continues to increase, the δ13C values become lighter and finally become heavier. Meanwhile, the carbon isotopes of C29βα, C30αβ, C30βα, and non-hopane gammacerane almost remain constant at different thermal stages. When the carbon isotopes of hopane compounds are used in the studies of oil–source correlation, it is prudent to consider the effects of thermal maturity on these values.